Implementing Intensity-modulated Radiotherapy with Simultaneous Integrated Boost for Anal Cancer: 3 Year Outcomes at Two Sydney Institutions. Issue 12 (December 2015) - Yates, A.; Carroll, S.; Kneebone, A.; Tse, R.; Horvath, L.; Byrne, C.; Solomon, M.; Hruby, G.
Abstract: Aims: Modern chemoradiotherapy used for the treatment of anal cancer has significant acute toxicity. Intensity-modulated radiotherapy (IMRT) may reduce these side-effects. We report our experience implementing IMRT with simultaneous boost at the Sydney Cancer Centre and Royal North Shore Hospital. Materials and methods: We retrospectively collected acute toxicity data on all consecutive patients treated definitively with IMRT between January 2008 and December 2011. Patients received concurrent 5-fluorouracil and mitomycin-C. The radiotherapy dose varied by stage in accordance with the Radiation Therapy Oncology Group (RTOG) 0529 protocol. The first 30 plans were evaluated for adherence to RTOG 0529 dose specifications. Locoregional control and survival outcomes were analysed in July 2014. Results: We included 42 patients (stage I 12%; II 41%; III 45%) with a median follow-up time of 43 months. At 3 years the locoregional control was 94% (95% confidence interval: 78–99), overall survival was 92% (95% confidence interval: 78–97), disease-free survival was 89% (95% confidence interval: 73–96), metastasis-free survival was 89% (95% confidence interval: 73–96) and colostomy-free survival was 89% (95% confidence interval: 72–96). There was no acute grade 4 toxicity. Acute grade 3 toxicity rates were: dermatological (33%), gastrointestinal (14%) and haematological (19%). Twenty-six per cent of patients were hospitalised for treatment-related toxicity. Only 12% required a treatment break greater than 3 days. All patients achieved RTOG 0529 planning target volume dose specifications. Most critical organ dose constraints were either met or met with minor deviation. The exception was 76% major deviation in small bowel constraints. Despite this no increase in gastrointestinal toxicity was observed. Conclusions: IMRT with simultaneous integrated boost is safe and well tolerated in an unselected population. Most dose specifications are achievable. Excellent locoregional control and survival outcomes are achievable outside of a clinical trial setting. Highlights: Intensity-modulated radiotherapy with simultaneous boost is safe and well tolerated by anal cancer patients. Excellent locoregional control (94%) and overall survival (89%) at 3 years. Acceptable grade 3 toxicity (skin: 33%; gastrointestinal: 14%; haematological: 19%) and low interruption rate.